Effect of Li2O substitution for Na2O on the solubility and water durability of Mo in aluminoborosilicate glass. (14th June 2021) - Gu, Yuxin; Liao, Qilong; Wang, Fu; Bin, Jia; Wang, Yuanlin; Xu, Youli; Zhu, Hanzhen; Zhou, Junjie; Luo, Yunlong; Zhu, Yongchang
Abstract: The effect of substitution of Li2 O for Na2 O on the solubility, crystallization of Mo in an aluminoborosilicate glass, and their aqueous durability were investigated. The results show that the substitution of Li2 O for Na2 O improves the depolymerization degree of the glass network by transferring part of [4] Al to [5] Al and [6] Al. When the Na2 O is all replaced by Li2 O, the solubility of Mo in the glass reaches 5 mol%. From the structural analysis, with the increase of the solubility of Mo in the glass, the depolymerization degree of the glass and the average modified cations field strength in the depolymerization region are also increased. After 28 days, the normalized leaching rates of Mo and B of all samples are about 10 −4 g·m −2 ·d −1 and 10 −3 g·m −2 ·d −1, respectively, and the normalized leaching rates of Mo decrease with the substitution of Li2 O for Na2 O. The results provide researchers and engineers with a potential way to improve the solubility of Mo in nuclear waste glasses.